Effect of Wideband Gap Tunnel Diode and Thickness of the Window Layer on the Performance of a Dual Junction Solar Cell. (2016) - Sahoo, Girija Shankar; Mishra, Guru Prasad
Abstract: Multi junction solar cells made up of III-V compound semiconductor has not achieved an optimized result yet. Tunnel diode plays an important role in the design of a highly efficient multi junction solar cell as it act as an interconnect layer between different sub cells. In this work we have investigated the effect of use of wideband gap tunnel diode and the window layer thickness on the performance of an InGaP/GaAs dual junction solar cell. The analysis is done under AM 1.5G spectrum using Synopsys Sentaurus TCAD. The electrical properties like external quantum efficiency, internal quantum efficiency, short circuit current density, open circuit voltage, spectral current density, and reflectance are examined and compared with GaAs tunnel diode solar cell. The conversion efficiency of the optimized cell is found to be 33.30%.